Sexual Functions in Men with Congenital Bilateral Absence of the Vas Deferens: A Retrospective Cross-sectional Study with Fertile Men - Akinsal, Emre Can; Baydilli, Numan; Tosun, Halil; Kızılay, Emrah; Sönmez, Gökhan (Urology Journal, 2025)
Purpose: To examine the sexual and psychological conditions of men with Bilateral Congenital Bilateral Absence of the Vas Deferens (CBAVD), a rare condition that contributes to male infertility, and compare it with healthy fertile men. Material and Methods: A total of 52 patients with CBAVD and 66 healthy, fertile men who attended our infertility and andrology clinic were included in the study. Patients with cognitive impairments, language barriers, significant comorbidities, or a history of urogenital surgery were excluded. Reproductive hormone levels and semen volumes were evaluated. In addition, sexual status was investigated with validated questionnaires such as the International Index of Erectile Function, Male Sexual Health Questionnaire, Arabic Index of Premature Ejaculation, Premature Ejaculation Diagnostic Tool, and Premature Ejaculation Profile. Results: In the CBAVD group, median total testosterone, FSH, LH levels, and semen volume were 401 ng/dL, 3.9 mIU/ml, 3.9 mIU/ml, and 0.9 ml, respectively. These parameters were 376 (ng/dL), 4.8 mIU/ml, 5 mIU/ml, and 3 ml in the control group. Semen volume was significantly lower in CBAVD men (p < 0.001). Questionnaires assessing erectile and ejaculatory function have shown that there was no significant difference between the CBAVD and control groups in terms of erectile function, orgasmic function, and sexual relationship satisfaction. However, sexual desire (p = 0.006) and overall satisfaction (p = 0.028) were found to be higher in the CBAVD group. Conclusion: The study suggests that CBAVD may not be a direct etiological factor for erectile dysfunction or premature ejaculation.